2021
DOI: 10.21608/eajbsz.2021.220560
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Acute Exposure Study of Abamectin Different Formulations Inducing Physiological and Oxidative Stress Biomarkers in Nile Tilapia, (Oreochromis niloticus).

Abstract: The goal of this study is to assess the acute and sublethal potential hazards on tilapia fish (Oreochromis niloticus) exposed to two different commercial formulations of abamectin (ABM, 5%): emulsifiable concentration (EC) and microemulsions (ME). The median lethal concentration (LC50 -96 h) to each formulation was determined, as well as the adverse effects of sublethal concentrations (½ LC50) on physiological and oxidative stress biomarkers after 96hs of exposure. The LC50 (96 h) values for EC and ME were 10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…In the present study, the fish exposed to 0.5 ug/l ABM exhibited a significant increase in the urea levels and reduction of the creatinine concentration. This is in line with the findings of Farag and Reda (2021) who found that fish exposed to ABM (5% EC) had considerably higher serum urea and lower creatinine levels after 96 h. Since the kidney is the organ that largely excretes urea, the increase in urea concentration may be linked to decreased kidney glomerular filtration, dysfunctional kidney tubules, and impaired kidney function (Magdy et al 2016;Walmsley and White 1994). On contrary, Mahmoud et al (2021) recorded a significant increase in O. niloticus exposed to 20.73 μg/l ABM for 84 days.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In the present study, the fish exposed to 0.5 ug/l ABM exhibited a significant increase in the urea levels and reduction of the creatinine concentration. This is in line with the findings of Farag and Reda (2021) who found that fish exposed to ABM (5% EC) had considerably higher serum urea and lower creatinine levels after 96 h. Since the kidney is the organ that largely excretes urea, the increase in urea concentration may be linked to decreased kidney glomerular filtration, dysfunctional kidney tubules, and impaired kidney function (Magdy et al 2016;Walmsley and White 1994). On contrary, Mahmoud et al (2021) recorded a significant increase in O. niloticus exposed to 20.73 μg/l ABM for 84 days.…”
Section: Discussionsupporting
confidence: 93%
“…On the contrary, the Labeo rohita juveniles fed with emamectin benzoate ≥ 250 μg kg −1 of fish biomass per day for 21 days had considerably high levels of ALP (Choudhary et al 2022). The marked increase in serum total protein, albumin, and globulin was recorded in O. niloticus exposed to ABM acute toxicity at 5 µg/l for 96 h (Farag and Reda 2021). In another study, abamectin was found to dramatically lower total protein concentration in tilapia fish tissues, including the liver, muscle, kidney, and gills (Al-Kahtani 2011).…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…In addition, ABM has a wide use as an antiparasite in farm animals [ 8 ]. Accordingly, ABM can flow from the application sites and reach aquatic ecosystems, causing harmful effects to non-target fish and other aquatic organisms, even at low levels (μg/L) [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%